Synthesis of superparamagnetic magnetite nanoparticles - A. Yu. Gervald; N. I. Prokopov; Yu. M. Shiryakina (Тонкие химические технологии)
The article is focused on the research of influence of various synthesis parameters (the rate of magnetite formation, iron salts mole ratio, nature and concentration of precipitator and process temperature) on the magnetic properties of magnetite nanoparticles.